Unusual Case of Superior Vena Cava Syndrome Caused by Intravascular Thyroid Metastasis - Vanesa Varela Pose; María Patricia Fierro Alanis; Anaberta Bermudez Naveira; Oskarina Lourdes Silva Gonzalez; Jorge Fernandez Noya; Urbano Anido Herranz; Rafael Lopez Lopez (Case Reports in Oncological Medicine)
Superior cava venous obstruction use to show a typical clinical presentation and a CT scan or even an ultrasonography can be sufficient to achieve an accurate diagnosis, but in this case, to obtain the final diagnosis, a multimodal assessment is needed. This case report shows a multidisciplinary approach which helped diagnose a complicated case, where conventional diagnostic methods were not enough.